Pengembangan Modul Eksperimen Fisika Berbasis Analisis Video pada Topik Mekanika untuk Siswa SMA - Pratama, Ardiansyah; Sugiyanto, Sugiyanto; Nugroho, Sunyoto Eko (UPEJ Unnes Physics Education Journal, 2020)
This study aims to develop an experimental module based on video analysis that can be used to improve student’s understanding. Using research and development (RnD) methods, we develope a model named Analysis, Design, Development, Implementation and Evaluation (ADDIE). The first step of this research is doing preliminary observations to find out the difficulties and observing the conditions of students. Furthermore, the next steps is developing the design and testing the design before being applied to students. The final step is evaluation by getting the response to the feasibility of this module. The results of feasibility test from the experts are 90.28% based on aspect of the content, 89,81% based on graphic presentation, 93,75% based on the linguistic aspect and overall getting a score 91.28% with very feasible criteria. The results of student’s cognitive aspects are obtained from measuring the increasing of students understanding in projectiole motion materials. This results showed improvement of students cognitive with score 0.5 which is in moderate category. The module implementation’s results showed a good response based on three aspects i.e aspect of use, aspect of learning and understanding, and aspect of presentation. Furthermore, the students responses for this module get the score of 74.39% which showed the proper criteria. In conclusions, this module can improve students understanding, and highly recommended for supporting physics learning, especially in physics experiments.